The Evaluation of Ed-Link Implementation in Teaching Students at STAIN Majene - Rina Marliana; Rismawati Rismawati; Rahmat Rahmat (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2023)
The Learning Management System (LMS) has been established in a number of universities worldwide to help connect students and lecturers without the confines of the traditional classroom. LMS is a software system to create web-based online lecture materials and manage learning activities and their results. Learning Management system has been implemented by several universities and it was really helpful for students and lecturers. One of the learning management system that is used in the teaching and learning process in STAIN Majene is Ed-Link. The existence of Ed-Link as a learning Management System is also support the development of ICT-based Learning among students and lecturers at STAIN Majene. The purpose of this research is to evaluate the implementation of Ed-Link as LMS in teaching and learning process between students and lecturers at STAIN Majene. Qualitative descriptive method will be used by researcherss in conducting this research. This research is a descriptive qualitative research which data collection is carried out by observing, interviewing and documenting. The research subject in this study is several lecturers and several students in STAIN Majene that have implemented Ed-Link in their Learning process. And the object of this research is to know the evaluation of ED-Link Implementation as LMS in Teaching Students. In the result of this research showed that there are positive and negative perceptions about Ed-link from the informants. From that perception, it will be the evaluation for Ed-Link implementation and the evaluation consist in teaching process and the evaluation for the feature in Ed-Link.